A METHOD FOR STRUCTURAL SYNTHESIS OF NETWORK CAPABLE APPLICATION PROCESSORS - Maykiv, I.; Stepanenko, A.; Wobschall, D. (International Journal of Computing, 2014)
A method for structural synthesis of Network Capable Application Processors (NCAPs) is proposed. It is based on a method of morphological analysis and synthesis and includes phases of functional analysis, structural synthesis, and search for a set of optimal solutions. The proposed method combines lexicographical criterion of preference (L- criterion) at a stage of functional analysis and unconditional criterion of preference (Pareto optimality) during the search phase, which are considered in literature as alternative methods of search for optimal solutions. Combining of criteria, makes it possible to reduce the number of synthesized alternative variants at a stage of structural synthesis and all obtained solutions are allowable.